2010
DOI: 10.1128/jb.00213-10
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphoenolpyruvate Phosphotransferase System Regulates Vibrio cholerae Biofilm Formation through Multiple Independent Pathways

Abstract: The bacterial phosphoenolpyruvate phosphotransferase system (PTS) is a highly conserved phosphotransfer cascade that participates in the transport and phosphorylation of selected carbohydrates and modulates many cellular functions in response to carbohydrate availability. It plays a role in the virulence of many bacterial pathogens. Components of the carbohydrate-specific PTS include the general cytoplasmic components enzyme I (EI) and histidine protein (HPr), the sugar-specific cytoplasmic components enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 66 publications
1
99
2
2
Order By: Relevance
“…The systems controlled by the PTS Ntr vary greatly among bacteria, from nitrogen fixation and polyhydroxybutyrate accumulation in Azotobacter vinelandii, to oligopeptide transport in Bradyrhizobium japonicum, pathogenesis in Brucella melitensis, biofilm formation in Vibrio cholerae, and potassium homeostasis and tricar- boxylic acid (TCA) cycle flux in E. coli (33)(34)(35)(36)(37)(38)(39). In S. meliloti, the PTS Ntr lacks membrane-bound transporters, making it strictly regulatory, and leaving the uptake of catabolites primarily to ABC and TRAP transporters (17).…”
Section: Discussionmentioning
confidence: 99%
“…The systems controlled by the PTS Ntr vary greatly among bacteria, from nitrogen fixation and polyhydroxybutyrate accumulation in Azotobacter vinelandii, to oligopeptide transport in Bradyrhizobium japonicum, pathogenesis in Brucella melitensis, biofilm formation in Vibrio cholerae, and potassium homeostasis and tricar- boxylic acid (TCA) cycle flux in E. coli (33)(34)(35)(36)(37)(38)(39). In S. meliloti, the PTS Ntr lacks membrane-bound transporters, making it strictly regulatory, and leaving the uptake of catabolites primarily to ABC and TRAP transporters (17).…”
Section: Discussionmentioning
confidence: 99%
“…This protein controls the expression of the manLMNO operon, which encodes the major glucose transporter of this human pathogen (78,150). However, ManR activity is regulated not by the components of the mannose-type PTS ManLMN but by the proteins of another mannose-type PTS, MpoABCD, a low-affinity glucose/mannose-specific PTS that functions mainly as glucose sensor (78 PTS components also play a role in biofilm formation, as has been shown for EI and HPr of V. cholerae (151). In a recent study, the utilization of mannitol by this organism was reported to activate biofilm formation and the expression of the vps genes, which encode the proteins required for the synthesis of the exopolysaccharides forming the biofilm matrix (152).…”
Section: Fig 5 Pts-catalyzed Glucose Uptake and The Eiiamentioning
confidence: 99%
“…Biofilm formation is also modulated by interplay between the positive transcription regulators, VpsT (Casper-Lindley & Yildiz, 2004) and VpsR (Yildiz et al, 2001), and the negative regulator, CytR (Haugo & Watnick, 2002). In addition, vps expression is modulated by the PhoBR two-component regulatory system (Pratts et al, 2009(Pratts et al, , 2010Sultan et al, 2010) and by components of the PTS phosphoryl cascade (Houot et al, 2008;, 2010a.…”
Section: Quorum Sensing Regulation Of Biofilm Formationmentioning
confidence: 99%
“…Pretreatment of mice with commensal bacteria engineered to express CAI-1 affords protection against a cholera challenge (Duan and March, 2010). A second set of attractive targets are the PTS components that modulate biofilm formation (Houot et al, 2008(Houot et al, , 2010(Houot et al, , 2010a. A comparative genomic analysis of 202 fully sequenced genomes (174 bacterial, 19 archaeal, and 9 eukaryotic) did not reveal components of the PTS system in eukaryotic cells (Barabote et al, 2005).…”
Section: Significance To Anti-virulence Drug Discoverymentioning
confidence: 99%